Projecting the Conceptual Provisions of the Socio-Economic Modernization of the Sphere of Goods Circulation - Melnyk Iryna M. (Bìznes Inform, 2018)
The article is aimed at substantiation of the conception of socio-economic modernization of the sphere of goods circulation. Orientation towards substantiation of the target conception of development of the sphere of goods circulation of national economy created possibility to formulate several advantages in the process of its socio-economic modernization. A conceptual scheme of implementation of the structural changes in the context of socio-economic modernization of the sphere of goods circulation is provided. Stages of developing the conception of socio-economic modernization of the sphere of goods circulation are structured. The author proposes measures as to legal-institutional, organizational-administrative, infrastructure-project-oriented, transport-logistics, and informational-communicational support for implementation of the processes of implementation of the concept of socio-economic modernization of the sphere of goods circulation. The author substantiates and detailizes structural components of the conception of the modernization of socio-economic sphere of goods circulation, i.e.: setting the target problem and analysis of the causes of its occurrence; substantiation of the strategic objective, setting goals and defining the terms of implementation of the concept; forming instruments, means, predictive scenarios of socio-economic modernization of the sphere of goods circulation; formalization of the expected results.